Online Third Places: Supporting Well-Being Through Identifying and Managing Unintended Consequences. (February 2022) - Parkinson, Joy; Schuster, Lisa; Mulcahy, Rory
Unintended consequences of service are important yet infrequently examined in transformative service research. This research examines an online service community that transformed into an online third place, with consumers socializing and forming lasting relationships. Using practice-informed theory-building and an abductive reasoning approach, findings are presented from both manual and automated coding of three qualitative data sets that form the basis of a case study examining an online weight management service forum. Extending beyond current conceptualizations of the third place, this study is the first to propose a framework delineating online third place characteristics and their impact on consumers' eudaimonic (the capacity for self-realization) and hedonic (attainment of pleasure and avoidance of pain) well-being. Findings show that in the absence of a physical or virtual servicescape, social factors including social density, equity, and personalization are key to constructing an online third place that supports well-being through building social connections and enjoyment. The new framework provides guidance for service managers to transform their online service communities into online third places to support consumer well-being and to identify and manage potential unintended consequences, for example, by ensuring segmentation of the community based on consumer groups' shared interests and consumer empowerment through participation.